ANALISIS FAKTOR-FAKTOR PEMBENTUK KONFLIK KERJA PEGAWAI (STUDI KASUS PADA SAMSAT SE-PULAU LOMBOK) - Saparudin Saparudin (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This study aims to find relevant main factors of conflict in SAMSAT Offices throughoutthe Island of Lombok. The study design includes an confarmatory research. Total respondent in thisstudy is 181 SAMSAT employees, but the actual data are based on 159 questionnaires. The maindata collection techniques are by using questionnaires, which were previously tested for their validityand reliability in other populations. Initial stage of data analysis are correlation test, KMO andBartlett's, anti-image correlation test, communalities, eigenvalues and the matrix componentsrotation. The conflict factors that are inputted in the factor analysis are 16 variables, whereas therelevant conflicts factors are only ten (10) including; workload variables, a job description,competition for resources, the dependence of the work, vagueness field tasks, the problem of status,social relationships, decision making, personnel policies and goal difference. The main conflict factorsare the main job description, the competition for resources, the dependence of the work, vaguenessfield tasks, the problem of status, social relationships and decision making. Those variables arecollected in the first factor are able to explain the variation conflict of 29.390 percent.Keywords: The Conflict Factors and Work Conflict.